India and Europe: An essay in philosophical understanding - Halbfass, Wilhelm (Delhi Motilal Banarsidas publishers Pvt. Ltd., 1990)
India and Europe share a dynamic relationship marked by cooperation in areas like trade, technology, and climate action, alongside significant challenges such as stalled free trade agreement (FTA) negotiations. The partnership is rooted in shared democratic values and focuses on strategic goals like green and digital transitions, with new agreements and collaborations expanding their engagement on security and sustainable development.